O1.3. DIFFERENTIAL HISTONE MODIFICATIONS IN 250 SCHIZOPHRENIA CASES AND 330 CONTROLS. (9th April 2019) - Girdhar, Kiran; Hoffman, Gabriel E; Jiang, Yan; Brown, Leanne; Devillers, Olivia; Shah, Hardik; Wang, Ying-chih; Zharovsky, Elizabeth; Jacobov, Rivka; Wiseman, Jennifer; Johnson, Jessica S; Kassim, Bibi S; et al.
Abstract: Background: Genomic dysregulation is likely to contribute to neuronal dysfunction in prefrontal cortex (PFC) and other brain regions affected in schizophrenia (SCZ), but genome-scale mapping of neuronal transcriptomes and epigenomes has not been conducted in larger cohorts. We have shown recently that the genomic landscape of open chromatin-associated histone modifications, including histone H3-acetyl-lysine 27 (H3K27ac), show in neurons significant associations with the genetic risk architecture of schizophrenia. Methods: We conducted H3K4me3 (H3K27ac) chromatin immunoprecipitation sequencing (ChIP-seq) on fluorescence-activated cell sorted (FACS) nuclei from dorsolateral PFC of 250 postmortem samples from SCZ and 280 matched control brains, generating altogether ~7(11) billion reads representing H3K4me3 (H3K27ac)-tagged nucleosomal DNA from PFC neurons. In addition, genotyping for the entire cohort of 530 brains was performed. Results: Enrichment of differentially modified regions across schizophrenia cases and controls in calcium and potassium signaling pathways. This finding was replicated in differentially modified regions across cases and controls obtained from independent cohort. In addition to this, enrichment of schizophrenia GWAS loci was observed in differentially modified regions across cases and controls. Discussion: Our dataset will provide unique insights into non-coding variants associated with neuronal dysfunction in schizophrenia. Our PsychENCODE sponsored resource highlights the critical role of cell-type specific signatures at regulatory and disease-associated non-coding sequences in the human frontal lobe. This is the first histone methylation and acetylation ChIP-seq datasets generated from prefrontal cortex brain region of 250 schizophrenia cases and 280 controls, postmortem human brain samples. As of now, this is the largest, yet unpublished ChIP-seq dataset from schizophrenia and control brains.